Nutritional psychiatry: implications for public health. (20th October 2021) - Jacka, F
Abstract: With depressive disorders the leading source of disability globally, the identification of new targets for prevention and management is imperative. The 20th century has seen major shifts in dietary intakes globally, with a marked increase in the consumption of sugars, snack foods, take-away foods and high-energy foods. At the same time, the consumption of nutrient-dense foods, such as high-nutrient vegetables and raw fruits, is diminishing. Poor diet is now recognized as the leading risk factor for illness and early mortality globally. However, there is now overwhelming body of evidence to tell us that unhealthy diet is also a key risk factor for psychiatric illnesses, including depression, anxiety and dementia. Current evidence highlights major developments in understanding the mechanistic pathways linking diet to neurodevelopmental and neurodegenerative outcomes. New research activities are underway in this field, however there is already a strong evidence for diet as a key strategy for improving mental and brain health. There is a need to address all the recent advances in the public health and policy imperatives and for translating the evidence into improvements to individual and population health.